961 Copenhagen psychosocial questionnaire-3(copsoq-3): turkish validation study. (24th April 2018) - Sahan, Ceyda; Baydur, Hakan; Demiral, Yucel
Abstract : Introduction: The Copenhagen Psychosocial Questionnaire-3 (COPSOQ-3), has been developed to assess psychosocial risks in the workplace. questionnaire consisted 25 dimensions as follows: work pace, quantitative demands, emotional demands, demands for hiding emotions (DHE), influence at work, possibilities for development, degree of freedom at work (DFW), meaning of work, commitment to the workplace, predictability, recognition, role-clarity, role-conflicts, quality of leadership, social support from colleagues, social support from supervisors, sense of community, insecurity over employment, insecurity over working conditions, work-life conflict, trust, organisational justice and job satisfaction. In total, COPSOQ-3-TR version included 78 items and 23 dimensions. The aim of the study was validation of the form of the COPSOQ-3 to Turkish language. Methods: This is a methodologic study. The field study has been carried out in three workplaces (Call centre, plastic and metal industry) Kaiser-Meyer-Olkin (KMO) Measure of Sampling Adequacy and Bartlett's Test of Sphericity were used to assess the suitability of the sample for factor analysis. Validity of the dimensions were investigated with exploratory factor analysis. The principal component analysis and varimax rotation methods used to identify the factor structure. The internal consistency was assessed by the Cronbach's alpha coefficient. Results: 807 respondents' questionnaires were evaluated. Fifty-seven percent of them were men. Mean age of men and women were 32.1±7.4, 27.1±6.6, respectively.Sampling adequacy was considered adequate (KMO=0.884). The factor analysis of COPSOQ-TR identified seventeen factors with eigenvalue higher than one and explained%63.6 of the total variance.The Cronbach's alpha values of 20 dimensions were found between 0.705 and 0.884. The Cronbach's alpha values of two dimensions (DHE and DFW) were found 0.638 and 0.643. The model is found that excellent fit (Chi-Square=5860.80, df=2672, P-value=0.00000, RMSEA=0.038, SRMR=0.05, CFI=0.97). Discussion: Findings have shown that Turkish version of the Copenhagen Psychosocial Questionnaire-3 is a reliable and valid instrument that can be considered useful tool to measure the psychosocial risks in Turkish population.